Obstetric complications - Calle M., Andrés (2015)
Molecular Biology of fetal asphyxia. Intrauterine growth restriction. Decision-making in cases of intrauterine growth restriction. New evidence in the management of placenta previa. Expectant management of mild gestational hypertensive disorders. Severe preeclampsia and HELLP syndrome. Prematurity situation in Peru. Cervical length in predicting preterm delivery. Use of antenatal magnesium sulfate to prevent cerebral palsy in premature infants. Pessary use in preterm birth. Use of misoprostol for postpartum hemorrhage. Multiple pregnancy antepartum management. Multiple pregnancy: intrapartum management, vaginal birth or caesarean ?.